X-treme sports and other action adventures - Sid Goldberg; MacNair, Marion; Marcil, Serge; Clermont, Christian; KOCH Vision (Firm) (Port Washington, NY : Koch Vision, 2005)
Takes sports to the extreme! Learn to fly like the wind when you take water skiing to a whole new level, speed down a hill at lightening speed with no brakes, hit the mountains to meet some Olympic snowboarders and gear up for some off road racing.
Title from container.
Animator, Bruce Simpson ; editors, Jason Levy, Zsolt Luka ; music, Christian Clermont ; wardrobe, Joanne Ho.
MPAA rating: Not rated.
DVD, region 1, full screen (1.33:1) presentation; Dolby Digital.
87695
Keywords: Extreme sports; Water skiing; Snowboarding; Extreme sports; Sports -- Television series; Youth -- Television series